Chromosomal localisation of a pseudoautosomal growth gene(s). - Ogata, Tsutomu; Petit, Christine; Rappold, Gudrun; Matsuo, Nobutake; Matsumoto, Takahiko; Goodfellow, Peter (Journal of medical genetics, 1992)
Although recent molecular studies in patients with sex chromosome aberrations are consistent with a growth gene(s) being present in the pseudoautosomal region (PAR), the precise location has not been determined. In this report, we describe a Japanese boy and his mother with an interstitial deletion in Xp22.3 and review the correlation between genotype and stature in six cases of partial monosomy of the PAR. The results indicate that the region from DXYS20 to DXYS15 is the critical region for the putative growth gene(s).